Implementasi Prinsip Ulangan 6:7 dalam Pendidikan Iman Anak di Keluarga Kristen (Implementation of the Principle of Repetition 6:7 in Children's Faith Education in Christian Families): Suatu Kajian Teologis dan Pedagogis (A Theological and Pedagogical Study) - Setiawan, Ruthnawaty; Soukotta, Dunant F.; Tan, Juan (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
Faith education in children is the primary responsibility of the Christian family, rooted in God’s command in Deuteronomy 6:7. However, in the modern context, many families have lost their spiritual function due to the influence of secular lifestyles and shifting social values. This article aims to examine and implement the principles of Deuteronomy 6:7 as theological and pedagogical foundations for children’s faith education in Christian families. The research employed a library research method with content analysis of biblical texts and Christian educational literature. The findings reveal that effective faith education requires synergy between parental example, love-based discipline, consistent prayer, and collaboration among the family, church, and faith community to nurture a generation deeply rooted in Christ. Contribution: This study contributes by reaffirming the vital role of the Christian family as the primary center of faith education grounded in the principles of Deuteronomy 6:7. Furthermore, it proposes an integrative model combining parental example, loving discipline, prayer, and church–family synergy to shape a contextually faithful generation in the modern era. Pendidikan iman anak merupakan tanggung jawab utama keluarga Kristen yang berakar pada perintah Allah dalam Ulangan 6:7. Namun, dalam konteks kehidupan modern, banyak keluarga kehilangan peran spiritualnya karena pengaruh gaya hidup sekuler dan perubahan nilai sosial. Artikel ini bertujuan untuk mengkaji dan mengimplementasikan prinsip Ulangan 6:7 sebagai dasar teologis dan pedagogis dalam pendidikan iman anak di keluarga Kristen. Metode penelitian yang digunakan adalah studi kepustakaan (library research) dengan pendekatan analisis isi (content analysis) terhadap teks Alkitab dan literatur pendidikan Kristen. Hasil penelitian menunjukkan bahwa pendidikan iman yang efektif membutuhkan sinergi antara keteladanan orang tua, disiplin yang berlandaskan kasih, doa yang konsisten, serta kerja sama antara keluarga, gereja, dan komunitas iman untuk membentuk generasi yang berakar pada Kristus. Kontribusi: Studi ini memberikan kontribusi dengan mempertegas pentingnya keluarga Kristen sebagai pusat utama pendidikan iman yang berakar pada prinsip Ulangan 6:7. Selain itu, penelitian ini menawarkan model integratif antara keteladanan, disiplin kasih, doa, dan sinergi gereja–keluarga dalam membentuk generasi beriman yang kontekstual di era modern.